Enhanced photoelectrocatalytic performance of TiO2 nanotube array modified with WO3 applied to the degradation of the endocrine disruptor propyl paraben - Martins, Alysson Stefan; Nuñez, Luciana; Lanza, Marcos Roberto de Vasconcelos [UNESP] (Elsevier, 2017)
We report on the photoelectrocatalytic degradation of the endocrine disruptor propyl paraben (PPB) using a TiO2 nanotube (TiO2-NT) electrode prepared via chemical anodization, and a TiO2-NT electrode modified with WO3 by electrodeposition. Solutions containing 50 mg L− 1 PPB were subjected to the photoelectrocatalytic process in a 0.2 L one-compartment electrochemical cell under UV/VIS irradiation, and the effects of bias potential (+ 0.5, + 1.0 and + 1.5 V) and solution pH (3.0, 7.0 and 10) on the performances of the unmodified and modified electrodes were investigated. Scanning electron micrographs (SEM) showed that the nanotubes were highly organized and perpendicularly aligned with a mean length of 800 nm. According to energy dispersive X-ray and SEM analyses, the concentration of W in the TiO2-NT/WO3 electrode was ~ 0.75% and the distribution of the modifier was continuous and homogeneous on the surface, with pores uncovered and decorated with WO3. The photocurrent of the TiO2-NT/WO3 electrode was improved by more than 20% in relation to its unmodified counterpart. The maximum degradation efficiencies were achieved at higher applied potentials and under acidic conditions for both electrodes. However, best results were obtained using the TiO2-NT/WO3 electrode with an applied potential of + 1.50 V and at pH 3. Under these conditions, more than 99% of PPB was removed in 30 min and 94% mineralization was achieved in 60 min. The photoactivity of the electrode was highly stable even after exhaustive application, indicating that WO3 deposition is an important method for improving the properties of TiO2-NT electrodes as applied to organic oxidation.
Keywords: Degradation; Electrodeposition; Endocrine disruptor; Mineralization; Photoactivity; Photoelectrocatalysis; Propyl paraben; TiO2-nanotube; TiO2-NT/WO3 electrode; Wastewater treatment; WO3